Exploring discursive barriers to contextual and sex-positive school-based sexual health education in policy documents in England : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology with endorsement in Health Psychology at Massey University, Manawatū, Aotearoa New Zealand - Ryan, Anita (Massey University, 2020)
England has implemented statutory reform related to school-based sexual health education, in the form of the Relationships Education, Relationships and Sex Education (RSE) and Health Education policy in 2019, which comes into effect from September 2020. In pursuance of effective and meaningful health promotion programmes in modern times where family forms, sexual identities, and sexual rights are continuously evolving, it is crucial to understand the ideologies, norms, and assumptions that influence the design and delivery of sexual health education. Therefore, this study was designed to critically analyse documents published by the UK government that are relevant to the long-awaited reform of school-based RSE. Based on a poststructuralist perspective, the research was conducted from a critical, social constructionist standpoint using discursive methodology. The analysis stems from the premise that policy documents can construct and reinforce specific versions of social reality that in turn support existing power relations and social structures. Without any intention to undermine the hard work that politicians have carried out in recent years; the goal was to locate potentially contradicting discourses within the highly politicised sphere of sexual health education. The aim was to identify discourses that may serve as barriers to provide adequate RSE that is relevant to the needs and lived experiences of young people. Within 13 relevant policy documents, four common ways that the discourse is deployed were identified, namely: (1) legal, (2) moral, (3) empowerment, and (4) rights-based discourses. Findings suggest that various underlying discursive issues are firmly in place that hinder the possibility of establishing an approved curriculum for RSE. In this thesis, I demonstrate how certain discourses transform the role of RSE in young people's lives from a supportive facet to one that condemns pupils’ sexual behaviour. The findings also point to the deficiency in official guidance on RSE. Guidance that is clear, effective, theory-based, and, refrains from controlling or managing young people’s sexual behaviour remains to be determined.
Keywords: 520304 Health psychology